Effects of adding mineral adsorbents to porous concrete for enhancing the quality performance of urban runoff systems. (6th August 2018) - Mousavi, Sayed-Farhad; Karami, Hojat; Farzin, Saeed; Teymouri, Ehsan
Abstract : Purpose: This study aims to use porous concrete and mineral adsorbents (additives) for reducing the quantity and improving the quality of urban runoff. Design/methodology/approach: The effects of adding mineral adsorbents and fine grains to porous concrete is tested for increasing its performance in improving the quality of urban runoff. Two levels of sand (10 and 20 per cent) and 5, 10 and 15 per cent of zeolite, perlite, LECA and pumice were added to the porous concrete. Unconfined compressive strength, hydraulic conductivity (permeability) and porosity of the porous concrete specimens were measured. Some of the best specimens were selected for testing the improvement of runoff quality. A rainfall simulator was designed and the quality of the runoff was investigated for changes in electrical conductivity (EC), total suspended solids (TSS), total dissolved solids (TDS) and chemical oxygen demand (COD). Findings: The results of this study showed that compressive strength of the porous concrete was increased by adding fine grains to the concrete mixture. Fine grains decreased the permeability and porosity of the samples. Zeolite had the highest compressive strength. Samples having pumice own maximum permeability. Samples which had perlite, had the least compressive strength and permeability. Because of the fast flow of runoff water in the porous slab and its low thickness, sufficient time was not provided for effective functioning of the additives, and the removal percentage of the pollution parameters was low. Originality/value: Porous concrete can ameliorate both quantity and quality of the urban runoff.